Effect of work and diet on dry matter intake, feed digestibility and nitrogen balance of F1 crossbred cows used for draught - Zerbini, E.; Gemeda, T.; Gebre-Wold, A.; Demissie, D. (Ethiopian Society of Animal Production, 1995)
Forty F1 crossbred dairy cows, 20 Friesian x Boran and 20 Simmental x Boran, in a 2 x 2 factorial arrangement (non working-non supplemented, non working-supplemented, working-non supplemented, and working-supplemented) were used to study the effect of work and diet supplementation on roughage intake, digestibility of nutrients, and nitrogen balance. Dry matter intake were greater for working than non working cows. Work and supplementation increased dry matter and organic matter in vivo digestibility. Passage rate and rumen mean retention of Cr-mordanted hay were similar for working and non working cows. Liquid turnover rate was lower and rumen liquid mean retention time was greater in working than non working cows whether supplemented or not. Nitrogen balance was negative for non supplemented cows during working periods compared to the same cows during rest periods. This seems to reflect mainly greater urine nitrogen excretion in working supplemented cows. Digesta kinetics could explain only partially the possible mechanisms responsible for greater roughage intake and digestibility in working cows.